PENGARUH AIR MINERAL DAN AIR MINUM BEROKSIGEN TERHADAP SATURASI OKSIGEN DARAH PESENAM ZUMBA - Pelealu, Brenda N. E.; Moningka, Maya E.W.; Rumampuk, Jimmy F. (Universitas Sam Ratulangi, 2015)
Abstract: During physical activity, blood flow and oxygen usage will increase in order to transport oxygen which is required by muscles during exercise. One of the parameters to check the amount of oxygen that is bound to hemoglobin is oxygen saturation. This study aimed to determine the level of blood oxygen saturation of those who consumed mineral water and high oxygenated water during zumba gymnastics. This was an analytical experiments method with pre and post test approach. Total samples were 31 people who met the criteria and were willing to become the respondents. Data were analyzed using Wilcoxon Test. The results showed that the oxygen saturation before and after consuming mineral water (97.5±0.9) and (97.7±1.03) meanwhile before and after consuming high oxygenated water (97.6±0.75) and (98.7±0.44). The Wilcoxon test showed that there was a significant difference of blood oxygen saturation between before and after consuming high-oxygenated water (p=0.000) whereas for other respondents who consumed mineral water, there was no significant difference in their condition before and after consuming mineral water (p=0.198). Conclusion: There was a higher increase in blood oxygen saturation value before and after consuming oxygenated water compared to before and after consuming mineral water.Keywords: oxygen saturation, mineral water, and oxygenated water.Abstrak: Ketika beraktivitas fisik, aliran darah dan penggunaan oksigen akan meningkat untuk mengangkut oksigen yang diperlukan pada otot selama latihan. Salah satu parameter untuk melihat kadar oksigen yang berikatan dengan hemoglobin adalah Saturasi Oksigen. Penelitian ini bertujuan untuk mengetahui nilai saturasi oksigen darah pada orang yang mengkonsumsi air mineral dan air beroksigen tinggi pada senam zumba. Penelitian ini menggunakan metode analitik eksperimental dengan pendekatan pre and post test. Sampel penelitian berjumlah 31 orang yang memenuhi kriteria dan bersedia menjadi responden. Analisis data dilakukan dengan menggunakan uji Wilcoxon test. Hasil penelitian menunjukkan bahwa saturasi oksigen sebelum dan sesudah mengonsumsi air mineral (97,5±0,9) dan (97,7±1,03) sedangkan sebelum dan sesudah mengonsumsi air beroksigen tinggi (97,6±0,75) dan (98,7±0,44). Hasil uji Wilcoxon test menunjukkan perbedaan yang signifikan pada responden sebelum dan sesudah mengonsumsi air beroksigen (p=0,000) sedangkan ketika responden mengonsumsi air mineral terdapat perbedaan yang tidak signifikan pada kondisi sebelum dan sesudah mengkonsumsi air mineral (p=0,198). Simpulan: Terjadi peningkatan yang lebih tinggi dalam nilai saturasi oksigen darah sebelum dan sesudah mengkonsumsi air beroksigen dibandingkan dengan air mineral.Kata kunci: saturasi oksigen, air mineral, air beroksigen.